Phylogenetic position and revised classification of Acacia s.l. (Fabaceae: Mimosoideae) in Africa, including new combinations in Vachellia and Senegalia - Kyalangalilwa, Bruce; Boatwright, James S.; Daru, Barnabas H.; Maurin, Olivier; van der Bank, Michelle (Botanical journal of the Linnean Society, 2013)
Previous phylogenetic studies have indicated that Acacia Miller s.l. is polyphyletic and in need of reclassification. A proposal to conserve the name Acacia for the larger Australian contingent of the genus (formerly subgenus Phyllodineae) resulted in the retypification of the genus with the Australian A. penninervis. However, Acacia s.l. comprises at least four additional distinct clades or genera, some still requiring formal taxonomic transfer of species. These include Vachellia (formerly subgenus Acacia), Senegalia (formerly subgenus Aculeiferum), Acaciella (formerly subgenus Aculeiferum section Filicinae) and Mariosousa (formerly the A. coulteri group). In light of this fragmentation of Acacia s.l., there is a need to assess relationships of the non‐Australian taxa. A molecular phylogenetic study of Acacia s.l and close relatives occurring in Africa was conducted using sequence data from matK/trnK, trnL‐trnF and psbA‐trnH with the aim of determining the placement of the African species in the new generic system. The results reinforce the inevitability of recognizing segregate genera for Acacia s.l. and new combinations for the African species in Senegalia and Vachellia are formalized. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 172, 500–523.